Vaccine knowledge among generation Y Malays in Pulau Pinang : a pilot study - Nur Hafeeza Ahmad Pazil; Muhamad Saiful Bahri Yusoff; Maslina Mohammed Shaed; Noor Alyani Nor Azazi; Sivamurugan Pandian; Intan Nooraini Haji Zainol; Nur Ayuni Mohd Jenol (Penerbit Universiti Kebangsaan Malaysia, 2022)
The increasing spread of infectious diseases in Malaysia has resulted the topic of vaccine acceptance and rejection is gaining traction in academia. the recent outbreak of the COVID-19 pandemic undoubtedly has manifested the never-ending debate of the topic of immunisation both academically and in public discourse. Thus, it is appropriate and timely to delve deeper into the ideas, norms, and values that influence people's health preferences and behaviour, particularly in vaccination. This study concerns on the perceived and actual vaccine knowledge of Generation Y Malays aged 25 to 40 years old in Pulau Pinang. It is critical to understand the public discussion vaccines within the framework of social interaction – how vaccines are portrayed and publicly understood. A pilot study was conducted prior to this to evaluate the procedure for participant recruitment, the data collection processes and the usability of the survey questionnaire. The improvements made to the instrument and methodology before beginning the main research study on vaccine knowledge among Malaysians in Pulau Pinang were made in an attempt to contribute to the body of research in this area.